Failure to launch?: The womens movement struggle for abortion decriminalization in the Portuguese Parliament (1982) - Prata,Ana (2012)
In 1982, the Communist Party presented a proposed law on abortion decriminalization and the womens movement tactics converged at parliamentary members. Despite that, we know little about this contested political process and the attempts for legal change that occurred from the interaction between activists, double-militants, and MPs. Findings show that womens organizations remained as outsiders and excluded from the political process, but that most of their preferred framings were put forward by their few political allies. The «failure» to pass abortion reform in 1982 cannot overshadow what the debate ultimately represented - a precursor of the approval of abortion decriminalization in Parliament just two years later, in 1984.